Nurse care during cardiorespiratory arrest in the emergency room (Research, Society and Development, 2022)
This research was structured with the objective of describing the nurse's assistance during cardiorespiratory arrest in the emergency room. This is a narrative review of the literature based on a literature search carried out in July 2020 in the respective data sources: Medical Literature Analysis and Retrieval System Oline (Medline) and Scientific Electronic Library Online (SciELO). The nurse is responsible for performing Basic Life Support (BLS) to maintain the circulation of the main vital organs and, secondly, to assist in Advanced Life Support (ALS), which aims to treat and revert to cardiac arrest. These professionals are responsible for administering drugs according to medical advice or protocol; bladder and nasogastric catheterization; performing the nursing evolution, checking medications and reorganizing the sector where the event took place, as well as providing assistance to family members, whether in cases of reversal of the arrest or in cases of deaths. In this perspective, nursing professionals need to appropriate their skills and make use of continuing education to promote the improvement of the quality of care for victims, since the success of interventions made in this clinical emergency depends on the level of preparation of professionals.